High incidence and poor prognosis of bone metastases in functioning small intestinal neuroendocrine tumors - Mathew, Annie; Hauptmeier, Pia; Schaarschmidt, Benedikt M.; Fendler, Wolfgang P.; Führer, Dagmar; Lahner, Harald (Frontiers in Endocrinology, 2025)
BackgroundThe prevalence and clinical relevance of bone metastases (BM) in advanced small intestinal neuroendocrine tumors (siNETs) is not well-documented.MethodsWe analyzed data from 458 patients (54% male, median age 58 years) with histologically confirmed siNETs treated at the ENETS Center of Excellence Essen from 2003 to 2023. BM occurrence and their impact on skeletal-related events (SREs) and overall survival (OS) were assessed using standardized DOTATOC-PET/CT within a consistent “one-stop shop” multidisciplinary care model.ResultsAt diagnosis, 305/458 patients (66.6%) had stage IV disease; BM were detected in 105/305 (34.4%). Functioning tumors were more frequent in BM patients (73%) than in the total cohort (40%). In 48.6% of patients, BM were initially visible on SSTR imaging only, becoming morphologically detectable after a median of 16 months. Most BM were osteoblastic (58%). During a median follow-up of 36 months, SREs occurred in 12.4% of BM patients, predominantly in those with osteolytic disease. SREs occurred in 27% of patients without antiresorptive therapy, but in none with treatment (p < 0.0001). Median OS was significantly shorter in patients with BM (127 vs. 170 months, p = 0.023), independent of age, sex or tumor grade.ConclusionBM are frequent in siNET, particularly in functioning tumors, and are associated with reduced survival. BM may initially be detectable only by functional imaging but becomes morphologically visible within less than 1.5 years. Antiresorptive therapy may reduce SREs. Whether adapting NET treatment algorithm for BM improves OS needs to be tested in clinical trials.